Digital Dialects: The Impact of Social Media on Language Evolution And Emerging Forms of Communication - Rini Ekayati; Berlin Sibarani; Siti Aisah Ginting; Rahmad Husein; Teguh Satria Amin (PT Inovasi Pratama Internasional, 2024)
The advent of social media has profoundly influenced language evolution, introducing novel linguistic trends and emergent forms of communication. This literature review, titled